2015
DOI: 10.1007/s13353-015-0316-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and evolutionary origins of farinin genes in Brachypodium distachyon L.

Abstract: Farinins are one of the oldest members of the gluten family in wheat and Aegilops species, and they influence dough properties. Here, we performed the first detailed molecular genetic study on farinin genes in Brachypodium distachyon L., the model species for Triticum aestivum. A total of 51 b-type farinin genes were cloned and characterized, including 27 functional and 24 non-functional pseudogenes from 14 different B. distachyon accessions. All genes were highly similar to those previously reported from whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…The chromosome starting position and the related position information of SAUR gene were obtained from the genome annotation file of Pyrus bretschneideri. The chromosome physical locations of the SAUR genes were mapped by MapInspect software (http:// mapinspect.software.informer.com, accessed on 9 September 2021) [44][45][46]. Genes and duplicates were ascribed to one of five different duplication categories: transposed, tandem, proximal, WGD, and dispersed [47].…”
Section: Chromosome Mapping Gene Duplication Events and Ka/ks Ratio A...mentioning
confidence: 99%
“…The chromosome starting position and the related position information of SAUR gene were obtained from the genome annotation file of Pyrus bretschneideri. The chromosome physical locations of the SAUR genes were mapped by MapInspect software (http:// mapinspect.software.informer.com, accessed on 9 September 2021) [44][45][46]. Genes and duplicates were ascribed to one of five different duplication categories: transposed, tandem, proximal, WGD, and dispersed [47].…”
Section: Chromosome Mapping Gene Duplication Events and Ka/ks Ratio A...mentioning
confidence: 99%
“…S2). Besides ALP genes reported in published studies (13, 23, 24), all other genes were cloned and sequenced ( SI Appendix , Table S1). Alignment of the translated amino acid sequences encoded by the 15 full-length TaALP genes showed that ALPs vary in length from 150 to 285 amino acids ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the study by Altenbach et al [55], the farinins (ALPs) comprised from 2.6 to 3.1% of the protein in the SDS-extractable polymeric proteins (EPP) and 1.9-2.4% of the protein in the SDS-unextractable polymeric proteins (UPP), and they were influenced by post-anthesis fertilizer. Both type b subunits (bx and by) of ALPs were reported to have non-functional pseudogenes in Brachypodium distachyon L accessions, Triticum dicoccoides, and T. aestivum [47,56]. Most recently, more novel alleles of ALP were found in Aegilops tauschii Coss.…”
Section: Introductionmentioning
confidence: 99%